NECESSITY OF MENTORING FOR THE DEVELOPMENT OF ENTERPRISES IN REZEKNE MUNICIPALITY - Zvaigzne, Anda; Kotāne, Inta; Znotiņa, Daina; Krivašonoka, Inita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The quality of the entrepreneurial environment is one of the preconditions for the competitiveness of the national economy of Latvia – the better conditions the government can create for entrepreneurs, the more investments are expected to be made in the national economy, which, in its turn, creates new jobs and raises the standard of living for the population. Mentoring is one of the most effective ways of transferring successful experience to enterprises by sharing knowledge, practical experience and contacts. In entrepreneurship, mentoring is mainly used to promote the growth of new and inexperienced enterprises. Cooperation between a mentor and a mentee creates opportunities for the growth and development of the mentee. The paper is based on the implementation results for the research grant "Mentoring Opportunities for Entrepreneurship Development in Rezekne Municipality”. The research aim is to examine the necessity of mentoring for the development of enterprises in Rezekne municipality. The research found that the difference between the numbers of registered and liquidated enterprises was insignificant. A survey of entrepreneurs revealed that the key factors that contributed to starting up a business were an opportunity to provide for the family, an opportunity to be independent and an opportunity to earn higher income. Upon starting up a business, potential mentors faced a lack of information/advice. Mentees, however, admitted that a lack of relevant experience and entrepreneurial ability was one of the most significant barriers to entrepreneurship development. The authors believe that mutual communication between potential mentors and mentees could avoid a lack of information/advice the mentees face, and sharing experience could contribute to the entrepreneurial ability of the mentees. The research employed the following methods: monographic and descriptive, analysis and synthesis, statistical analysis and a sociological method – a survey of entrepreneurs. The research was done based on research papers, data of the Central Statistical Bureau of Latvia and other information sources.